Plastic use for food and drinks and related knowledge, attitudes, and practices among a sample of Egyptians - Hassan, Fatma Mohamed; El Desouky, Eman D.; Salem, Marwa Rashad; Abdelsabour, Motaze Adel; Abdelmoneim, Mostafa Alaa; Elsaieed, Mohamed Mahmoud; Ali, Mona Mohamed (Frontiers in Public Health, 2023)
Introduction: Plastic is extensively used in everyday life, particularly for food and beverage containers. The inappropriate use of these containers may lead to the leaching of various chemicals from plastic, such as bisphenol A, phthalate, and styrene, which cause numerous adverse health effects. This study aimed to assess the knowledge, attitudes, and practices toward using plastic for food and drinks among a sample of the Egyptian population. Materials and Methods: A questionnaire was designed based on scientific literature to assess sociodemographic data, knowledge, attitudes, and practices toward using of plastic for food and drinks. A total of 639 participants were recruited using the convenience sampling technique. Results: More than half of the participants (347,54.3 %) had poor knowledge scores, in contrast to a good attitude reported by the majority (515, 80.6%). The majority (493, 77.2 %) were occasional and frequent plastic users. Statistically significant relationships were observed between the mean knowledge, attitude, and practice scores and all the studied demographic characteristics except the marital and working status for knowledge, the socioeconomic status for attitude, and gender and residence for practice. Conclusion: The majority of the participants had unsatisfactory knowledge and improper practices regarding the appropriate uses of plastic for food and beverages, which necessitates implementation of public awareness programs about the safe uses of plastic.